Activation and Repolarization of the Normal Human Heart under Complete Physiological Conditions - Ramanathan, Charulatha; Jia, Ping; Ghanem, Raja; Ryu, Kyungmoo; Rudy, Yoram (Proceedings of the National Academy of Sciences - PNAS, 2006)
Knowledge of normal human cardiac excitation stems from isolated heart or intraoperative mapping studies under nonphysiological conditions. Here, we use a noninvasive imaging modality (electrocardiographic imaging) to study normal activation and repolarization in intact unanesthetized healthy adults under complete physiological conditions. Epicardial potentials, electrograms, and isochrones were noninvasively reconstructed. The normal electrophysiological sequence during activation and repolarization was imaged in seven healthy subjects (four males and three females). Electrocardiographic imaging depicted salient features of normal ventricular activation, including timing and location of the earliest right ventricular (RV) epicardial breakthrough in the anterior paraseptal region, subsequent RV and left ventricular (LV) breakthroughs, apex-to-base activation of posterior LV, and late activation of LV base or RV outflow tract. The repolarization sequence was unaffected by the activation sequence, supporting the hypothesis that in normal hearts, local action potential duration (APD) determines local repolarization time. Mean activation recovery interval (ARI), reflecting local APD, was in the typical human APD range (235 ms). Mean LV apex-to-base ARI dispersion was 42 ms. Average LV ARI exceeded RV ARI by 32 ms. Atrial images showed activation spreading from the sinus node to the rest of the atria, ending at the left atrial appendage. This study provides previously undescribed characterization of human cardiac activation and repolarization under normal physiological conditions. A common sequence of activation was identified, with interindividual differences in specific patterns. The repolarization sequence was determined by local repolarization properties rather than by the activation sequence, and significant dispersion of repolarization was observed between RV and LV and from apex to base.